2012
DOI: 10.1101/gr.136507.111
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin regulates tissue-specific expression by stabilizing highly occupied cis-regulatory modules

Abstract: The cohesin protein complex contributes to transcriptional regulation in a CTCF-independent manner by colocalizing with master regulators at tissue-specific loci. The regulation of transcription involves the concerted action of multiple transcription factors (TFs) and cohesin's role in this context of combinatorial TF binding remains unexplored. To investigate cohesin-non-CTCF (CNC) binding events in vivo we mapped cohesin and CTCF, as well as a collection of tissuespecific and ubiquitous transcriptional regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
185
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(207 citation statements)
references
References 72 publications
(102 reference statements)
16
185
5
1
Order By: Relevance
“…In addition, cohesin contributes to the regulation of gene expression by mechanisms thought to involve long-range interactions between its binding sites at regulatory elements associated with CTCF (Parelho et al 2008;Rubio et al 2008;Stedman et al 2008;Wendt et al 2008) or with active promoters and enhancers (Misulovin et al 2008;Kagey et al 2010;Schmidt et al 2010;Faure et al 2012;Dorsett and Merkenschlager 2013). Taken together these properties suggest a role for cohesin in genome organization.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, cohesin contributes to the regulation of gene expression by mechanisms thought to involve long-range interactions between its binding sites at regulatory elements associated with CTCF (Parelho et al 2008;Rubio et al 2008;Stedman et al 2008;Wendt et al 2008) or with active promoters and enhancers (Misulovin et al 2008;Kagey et al 2010;Schmidt et al 2010;Faure et al 2012;Dorsett and Merkenschlager 2013). Taken together these properties suggest a role for cohesin in genome organization.…”
mentioning
confidence: 59%
“…Raw read alignment, filtering, and peak-calling for RAD21, MED1, NIPBL CTCF, and definition of CNCs was done as previously described (Faure et al 2012). ChIP-seq data for H3K27me3 (Zhang et al 2012) was similarly processed, except CCAT version 3.0 (Xu et al 2010) was used to identify the relatively broad regions occupied by this mark (precompiled histone modification configuration).…”
Section: Chip-seq Read Mapping and Peak Callingmentioning
confidence: 99%
“…This supports the idea that different functions may be a result of the context of CTCF binding (Gaszner and Felsenfeld 2006), and it is possible that coordinate binding of cohesin may influence CTCF. Cohesin is involved in tissue-specific transcriptional control (Faure et al 2012) and associated with the Mediator complex, which has a role in transcriptional activation (Taatjes 2012). Studies have shown a link between cohesin, the Mediator complex, transcription, and chromatin looping (Kagey et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of cohesin results in reduced DNA accessibility and transcription factor binding, indicating a causative role for cohesin in promoting the formation of these transcription factor clusters . Cohesin may thus help to confer robustness in gene expression by helping to stabilize highly occupied cis-regulatory modules (Faure et al, 2012) (Fig. 1).…”
Section: Chromatin Organization In Pluripotent Cellsmentioning
confidence: 99%